Amoebae, Giant Viruses, and Virophages Make Up a Complex, Multilayered Threesome - Diesend, Jan; Kruse, Janis; Hagedorn, Monica; Hammann, Christian (Frontiers in Cellular and Infection Microbiology, 2018)
Viral infection had not been observed for amoebae, until the Acanthamoeba polyphaga mimivirus (APMV) was discovered in 2003. APMV belongs to the nucleocytoplasmatic large DNA virus (NCLDV) family and infects not only A. polyphaga, but also other professional phagocytes. Here, we review the Megavirales to give an overview of the current members of the Mimi- and Marseilleviridae families and their structural features during amoebal infection. We summarize the different steps of their infection cycle in A. polyphaga and A. castellani. Furthermore, we dive into the emerging field of virophages, which parasitize upon viral factories of the Megavirales family. The discovery of virophages in 2008 and research in recent years revealed an increasingly complex network of interactions between cell, giant virus, and virophage. Virophages seem to be highly abundant in the environment and occupy the same niches as the Mimiviridae and their hosts. Establishment of metagenomic and co-culture approaches rapidly increased the number of detected virophages over the recent years. Genetic interaction of cell and virophage might constitute a potent defense machinery against giant viruses and seems to be important for survival of the infected cell during mimivirus infections. Nonetheless, the molecular events during co-infection and the interactions of cell, giant virus, and virophage have not been elucidated, yet. However, the genetic interactions of these three, suggest an intricate, multilayered network during amoebal (co-)infections. Understanding these interactions could elucidate molecular events essential for proper viral factory activity and could implicate new ways of treating viruses that form viral factories.